Characterization of Geriatric Dysphagia Diagnoses in Age-Based Cohorts. Issue 3 (July 2020) - Applebaum, Jeremy; Lee, Emerson; Harun, Aisha; Davis, Ashley; Hillel, Alexander T.; Best, Simon R.; Akst, Lee M.
Objective: An aging population requires increased focus on geriatric otolaryngology. Patients aged ≥65 years are not a homogenous population, and important physiologic differences have been documented among the young-old (65-74 years), middle-old (75-84), and old-old (≥85). We aim to analyze differences in dysphagia diagnoses and swallowing-related quality-of-life among these age subgroups. Study Design: Retrospective chart review. Setting: Tertiary care laryngology clinic. Subjects and Methods: We identified chief complaint, diagnosis, and self-reported swallowing handicap (Eating Assessment Tool [EAT-10] score) of all new patients aged ≥65 years presenting to the Johns Hopkins Voice Center between April 2015 and March 2017. Dysphagia diagnoses were classified by physiologic etiology and anatomic source. Diagnostic categories and EAT-10 score were evaluated as functions of patient age and sex. Results: Of 839 new patients aged ≥65 years, 109 (13.0%) reported a chief complaint of dysphagia and were included in this study. The most common dysphagia etiologies were neurologic and esophageal. Most common diagnoses were diverticula (15.6%), reflux (13.8%), and radiation induced (8.3%). Diverticula, cricopharyngeal hypertonicity, and radiation-induced changes were associated with higher EAT-10 score ( P < .001). Significant differences by sex were found in anatomic source of dysphagia, as men and women were more likely to present with oropharyngeal and esophageal disease, respectively ( P = .023). Dysphagia etiology and EAT-10 score were similar across age subgroups. Conclusion: Important differences among dysphagia diagnosis and EAT-10 score exist among patients aged ≥65 years. Knowledge of these differences may inform diagnostic workup, management, and further investigations in geriatric otolaryngology.